Autismo e mediação: interfaces com o Caps IJ - Reali, Victória Giacomin; Lucero, Ariana (Analytica: Revista de Psicanálise, 2025)
The article aims to reflect on psychoanalytic practice in relation to mental health, focusing on mediation techniques involving autism within the public system, particularly in Child and Adolescent Psychosocial Care Centers (CAPS IJ). It discusses therapeutic groups as an interesting work modality for children who exhibit difficulty in establishing social bonds. In this context, it explores the possibility of the institution offering workshops that consider the knowledge as situated on the child’s side, while the analyst’s approach should be guided by a unique perspective on the patients’ interests, in a detail-oriented clinical approach. This is a literature review that considers the theoretical contributions of Lacanian psychoanalysis, which highlights the voice as a primary object in the constitution of the autistic subject. The research references the recent publication by J-M. Vives and Isabelle Orrado (2021), Autism and Mediation, where the authors supports psychoanalytic interventions through the concept of mediation, emphasizing the invoking drive.